The relative efficiency of active labour market policy: Evidence from a social experiment and non-parametric methods - Johan Vikström; Michael Rosholm; Michael Svarer (Institute for Labour Market Policy Evaluation (IFAU), 2011)
We reanalyze the effects of a Danish active labour market program social experiment, that included a range of sub-treatments, including monitoring, job search assistance and training. Previous studies have shown that the overall effect of the experiment is positive. We apply newly developed non-parametric methods to determine which of the individual policies that explains the positive effect. The use of non-parametric methods to separate sub-treatment effects is important from a methodological point of view, since the alternative, namely parametric/distributional assumptions, is in conflict with the concept of experimental evidence. Our results are highly relevant in a policy perspective, as optimal labour market policy design requires knowledge on the effectiveness of specific policy measures.
Keywords: C14; C41; C93; 330; Active labour market policy; treatment effect; non-parametric bounds; Arbeitsmarktpolitik; Statistische Bestandsanalyse; Nichtparametrisches Verfahren; Dänemark